English teachers' and lecturers' perceptions of reflective practice through video recording at the teacher certification program - Sitti Fatimah; Yuli Tiarina; Fitrawati Fitrawati; Asri Sekar Mira (Universitas Syiah Kuala, 2021)
Considering the long-recognized contribution of reflective practice on teachers’ continuous professional development, this article casts new light in reporting English teachers’ and lecturers’ perceptions on the needs to implement reflective practice through video recording during peer teaching in the Indonesian Teacher Certification Program. This needs analysis is conducted as the preliminary step of the Research and Development (RD) project and the data will be taken as the basis for the development of reflective practice model with video recording in peer teaching. The perceptions of the needs were collected through a closed and open-ended questionnaire distributed to two groups of respondents. The first group consisted of pre- and in-service English teachers who participated in the PPG (Pendidikan Profesi Guru) Program, or Teacher Certification Program, during the course of 2018 and 2019; and are now teaching secondary school students within the provinces of West and North Sumatra, Aceh, Jambi, and Riau. The second group was lecturers at the English Language Education Program (ELEP) of Universitas Negeri Padang teaching at the PPG Program. The findings show that most teachers believed that reflective practice using video recording enabled them to see their teaching strengths and weaknesses and, in return, would be able to improve students’ learning outcomes. Similarly, all lecturers also believed that the needs of reflective practice assisted by digital technologies are highly important. In general, the perceptions of these two groups of respondents demonstrate the crucial needs of implementing reflective practice with video recording during peer teaching in the PPG Program.